Influencia del estrés postraumático en el bienestar psicológico en usuarios externos del Centro de Salud Mental Comunitarios Vitaliza Ica, 2021 - Araujo Meza, Katlyn Patricia (2022)
Objective: To determine the influence of post-traumatic stress on psychological well-being in external users of the community mental health center Vitaliza Ica, 2021. Material and method: Prospective, cross-sectional and explanatory-level study, the sample consisted of 88 external users of the Vitaliza community mental health center, who responded to a questionnaire with characterization variables and a scale-type instrument of 21 items for the variables of symptoms of stress disorder and 39 items for the variable of psychological well-being. The results were sent descriptively and the Spearman Rho test was used. Results: Of the participants, 58% were female, 38.6% corresponded to ages 31 to 40, 53.4% belonged to high school education and 36.4% were single. 75% present a low level of post-traumatic stress, 14.8% medium and 10.2% high. In addition, with regard to psychological well-being, 44.3% present a low level, 22.7% moderate, 25% high and 8% high. Conclusion: There is an influence of post-traumatic stress on psychological well-being in external users of the community mental health center Vitaliza Ica 2021. Keywords: Post-traumatic stress, well-being, mental health. (source: DeCS BIREME).